Variations in resistance against Phthorimaea operculella in wild potato tubers - Horgan, Finbarr G.; Quiring, Dan T.; Lagnaoui, Aziz; Salas, Alberto R.; Pelletier, Yvan (Wiley, 2010)
Tuber resistance can contribute to current management strategies against the potato tuber moth, Phthorimaea operculella Zeller (Lepidoptera: Gelechiidae), in field and stored potatoes. Wild potatoes represent a potential source of novel resistance traits against the moth. We assessed resistance in three wild potato species, Solanum multiinterruptum Bitt., Solanum sparsipilum (Bitt.) Juz. and Buk., and Solanum wittmackii Bitt. against neonate and developing tuber moth larvae. All three species had high levels of resistance but accessions of S. sparsipilum and S. wittmackii were significantly more resistant. Resistance in S. multiinterruptum was generally concentrated in the tuber periderm, whereas in S. sparsipilum and S. wittmackii resistance was mainly cortex‐based. Unidentified cortex‐resistance factors in all three species reduced survival and increased larval and pupal development times, but had no apparent effects on the pupal weights of survivors. A high proportion of larvae abandoned or died within tubers of S. wittmackii, which has particularly high levels of unidentified cortex‐based defenses. Resistance decreased in S. multiinterruptum and S. sparsipilum as tubers sprouted but was more stable in S. wittmackii. Periderm‐based resistance was more stable than cortex‐based resistance in S. multiinterruptum during sprouting. In contrast, cortex‐based resistance was stable in tubers of S. wittmackii as these sprouted, and resistance may have increased on some older sprouting tubers. Solanum multiinterruptum and S. sparsipilum are proposed as potential sources of resistance against the potato tuber moth.